Monitoreo de las poblaciones de mosca de la fruta y su incidencia en los bosques naturales de chirimoya (Annona cherimola mill.) en la provincia de Loja. - Minga Cango, Cristian Eduardo (2018)
Originally from southern Ecuador and northern Peru, the Cherimoya (Annona Cherimola Mill.) is a fruit with organoleptic and nutritional characteristics appreciated by consumers around the world. However, in our country its commercial use is undervalued, most of the production is linked to local markets and small producers. The limited information on agronomic management keeps producers at the mercy of several difficulties, among them important pests for fruit growing such as the fruit fly. The objective of this research work was to monitor the fruit fly populations and their incidence in the natural cherimoya forests in the province of Loja, was carried out in four areas of the province identified as producers of this fruit, these were: Chirimoyal, Yuma, Tacoranga and El Salado. The monitoring process was carried out through the establishment of trapping networks and fruit sampling. With the information obtained, the number of species per place, population dynamics and percentages of infestation and parasitism were determined. The identification of the specimens made in the laboratory determined the presence of two genera and 10 species of fruit fly. The population with the greatest number of individuals corresponds to the Anastrepha fraterculus species, whose percentage of catches always remained above 75%. Similarly, a total of 40.64 Kg of fruits of different varieties of cherimoya were examined and it was reported that they were only infested by the species A. fraterculus in each of the four sectors of study. The percentages of parasitism were below 2% and the presence of two species was reported: Doryctobracon crawfordi and Sycophila sp., Only the El Salado sector did not register the presence of parasitoids.